Carbon-track localisation as an adjunct to wire-guided excision of impalpable breast lesions: A retrospective cohort study. (2019) - Tran, Q.; Mizumoto, R.; Tran, M.C.; Reintals, M.; Gounder, V.
Abstract: Background: Wire-guided localisation (WGL) is the most widely used approach to excise impalpable breast lesions in breast conserving surgery (BCS). There are several disadvantages to this technique. There are a variety of methods available, each with its own imperfections, therefore a superior approach is much desired. Here we report the efficacy of carbon-track localisation (CL) as an adjunct to hookwire in terms of margins, complications and operating time. Methods: A consecutive series of patients with impalpable breast lesions undergoing either CL combined with WGL or just WGL alone from 2016 to 2017 were evaluated in this retrospective cohort study. Of 57 patients, 27 CLs with WGL and 30 WGLs alone were performed. Results: All breast lesions were successfully localised pre-operatively and excised in both groups. Involved margins for invasive or in-situ disease were found in 14% in the CL group and 24% in the WGL group ( p = 0.70). Close margins of <1 mm were found in 29% of the CL group and 48% in the WGL group ( p = 0.34). The median operating time were 26 min and 37 min for the CL and WGL groups respectively ( p = 0.002). Complications were noted to be 7.4% with CL and 16.7% with WGL ( p = 0.43). Conclusion: Carbon-track as an adjunct to hookwire localisation can be easily adopted and has a short learning curve with improved surgical outcomes. Although requiring further validation from larger studies to demonstrate statistical significance, the outcomes reported here are promising. Highlights: Wire-guided localisation is the most widely used technique to excise impalpable breast lesions. Several drawbacks are associated with this method and there is a desire for a better approach. Carbon-track has the potential to be a better option, either in combination or as an independent alternative to hookwires.